TOXIC MASCULINITY AND LOCAL WISDOM OF THE BUGIS CULTURE IN EAST LUWU REGENCY - Syamsuddin, Naidin; Nursyamsi, Nursyamsi; Erwin, Erwin (Al-Qalam, 2023)
The purpose of this research is to examine how the values of Sipakatau, Sipakainge, and Sipakalebbi are applied in the Bugis culture, how toxic masculinity emerged in the East Luwu Regency, and how these values help people overcome toxic masculinity. This study employed a qualitative descriptive approach, utilizing data collection methods such as observation, interviews, and documentation. The data analysis was conducted through data reduction, presentation, and conclusion. The study findings indicate that the Bugis culturein East Luwu Regency continues to strongly uphold the values of Sipakatau, Sipakainge, and Sipakalebbi in their daily lives. The Bugis culture in East Luwu Regency has largely rejected the patriarchal culture that fosters toxic masculinity, although there are still some villages that uphold this cultural norm. Furthermore, the values of Sipakatau, Sipakainge, and Sipakalebbi play a crucial role in addressing social conflicts, particularly the issue of toxic masculinity in East Luwu Regency. This study suggests that it offers insights into the significance of safeguarding the cultural values of Sipakatau, Sipakainge, and Sipakalebbito address social conflicts.